2017
DOI: 10.1097/njh.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Familial Interaction Patterns During the Palliative Phase of a Family Member Living With Cancer

Abstract: This study aimed to illuminate aspects of familial interactions when 1 member is in the palliative phase of his/her cancer course. An individual cancer diagnosis influences the entire family, often requiring daily life changes for all members. Current research has examined individual family member perspectives; family system nursing studies are warranted. Narrative family interviews were conducted on 13 families living with cancer. The interviews were transcribed and analyzed according to a hermeneutic method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…24 As in previous studies, one of the most important coping methods for the patients was continuing the daily routines. 3,9,[25][26] The patients identified the support of friends and family as a positive, empowering factor, which is in line with the findings of many previous studies. 9,12,25,[27][28] In this study patients estimated that their relationship with their family had become closer because of the illness and the support of their spouse or partner was similarly described as invaluable, as Koffman et al (2012) and Möllerberg at al.…”
Section: The Coping Processes Of Incurable Cancer Patientssupporting
confidence: 90%
See 1 more Smart Citation
“…24 As in previous studies, one of the most important coping methods for the patients was continuing the daily routines. 3,9,[25][26] The patients identified the support of friends and family as a positive, empowering factor, which is in line with the findings of many previous studies. 9,12,25,[27][28] In this study patients estimated that their relationship with their family had become closer because of the illness and the support of their spouse or partner was similarly described as invaluable, as Koffman et al (2012) and Möllerberg at al.…”
Section: The Coping Processes Of Incurable Cancer Patientssupporting
confidence: 90%
“…In nursing, it is vital to bear in mind that patients remain part of their families and communities regardless of their illness. [1][2][3] The World Health Organization (WHO 2017) takes all these issues into account by defining palliative care as the active and holistic treatment of patients with an incurable or life-threatening illness and their loved ones. The objective of such treatment is not only to relieve symptoms but also to guarantee the best possible quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…While this study was being planned, only two studies were found which had the specific objective of exploring experiences and needs in family relationships in cases of cancer in the palliative phase (Badr & Taylor, 2006;Gardner, 2008). When the study was being summarised, a further three studies had been added (Drabe et al, 2016;Fergus & Gray, 2009;Møllerberg et al, 2017). Because few studies were found with the specific objective of exploring experiences and needs in family relationships, studies with other objectives were also included (e.g.…”
Section: Family Relationships During Cancer In the Palliative Phasementioning
confidence: 99%
“…To be together, live a normal life and have a positive attitude to the situation is important for patients and family members at the end of life (Foxwell & Scott, 2011;James et al, 2007;Molassiotis et al, 2011). Two studies connect family solidarity with the perception of being a family (Carlander et al, 2011;Møllerberg et al, 2017). Family solidarity is also linked to successful coping and a feeling of control over the situation (Carlander et al, 2011;Foxwell & Scott, 2011;Molassiotis et al, 2011).…”
Section: Family Relationships During Cancer In the Palliative Phasementioning
confidence: 99%
See 1 more Smart Citation